Lemon Peel Extract for Synthesizing Non-Toxic Silver Nanoparticles through One-Step Microwave-Accelerated Scheme - Jahan, Israt; Isildak, Ibrahim (KAHRAMANMARAS SUTCU IMAM UNIV REKTORLUGU, 2021)
In this study, biofunctionalized globular or oval shaped silver nanoparticles were obtained by using aqueous extract of lemon peel (Citrus limon) via microwave-accelerated heating system. While UV-visible spectroscopy, FTIR and XRD analyses were applied to recognize the formation of nano-silver, TEM and Zeta analysis were employed to reveal their morphological features. UV-vis spectrum of fabricated AgNPs indicated its characteristic maximum absorbance at 445 nm. Phytosynthesized silver nanoparticles were poly-dispersed with Z-average value of 41.86 nm, and showed excellent stability for several months with no aggregation and agglomeration. The non- toxic nature of the developed Ag nanoparticles was further confirmed by applying on healthy mouse fibroblast L929 cell line, which may expand their potentials for further studies related to medical science and other biological applications.
Keywords: Lemon peel; Microwave-assisted green synthesis; Non-toxic AgNPs; Nanoscience; ASSISTED GREEN SYNTHESIS; MEDIATED SYNTHESIS; CITRUS PEEL; IN-VITRO; BIOSYNTHESIS; CYTOTOXICITY; ANTIBACTERIAL; Agriculture